Tectonics of Sedimentary Basins : Recent Advances. - Busby, Cathy, 1951- (John Wiley & Sons, 2011)
Investigating the complex interplay between tectonics and sedimentation is a key endeavor in modern earth science. Many of the world's leading researchers in this field have been brought together in this volume to provide concise overviews of the current state of the subject. The plate tectonic revolution of the 1960's provided the framework for detailed models on the structure of orogens and basins, summarized in a 1995 textbook edited by Busby and Ingersoll. Tectonics of Sedimentary Basins: Recent Advances focuses on key topics or areas where the greatest strides forward have been made, while.